COMPLICATIONS OF LAPAROSCOPIC CHOLECYSTECTOMY: AN EXPERIENCE OF 247 CASES - Farooq, Umar; Rashid, Tariq; Naheed, Asma; Barkat, Najeeb; Iqbal, Muhammad; Sultana, Qamar (Journal of Ayub Medical College Abbottabad, 2015)
Background: Laparoscopic cholecystectomy needs lot of training and experience in developing countries like Pakistan. After the introduction of laparoscopic cholecystectomy several studies have been conducted to evaluate the complications of laparoscopic cholecystectomy and to establish the efficacy and safety of the procedure.The aim of this study was to determine the complications of laparoscopic cholecystectomy in a teaching hospital during the learning process. Methods: This descriptive case series was conducted in the department of General Surgery at Social Security Teaching Hospital, Islamabad, from October 2012 to February 2015. Patients of more than 15 years of age having symptomatic gallstones were included. Patients with dilated common bile duct (>8 mm in diameter), jaundice, acute cholecystitis, mass at porta hepatis and positive hepatitis B or C virology were excluded. Results: A sample of 247 consecutive patients was studied. Of them, 218 (88.26%) were females and 29 (11.74 %) were males. Their age ranged from 15 to 73 years (mean 43.37). Six (2.43%) patients developed epigastric port site wound infection. Four patients (1.62%) had bleeding. There was bile leakage in 2 (0.82 %) patients postoperatively. Two patients (0.82%) had collection (haematoma) in pouch of Morrison. One patient (0.41%) had duodenal injury. Eighteen (7.29 %) laparoscopic procedures were converted to open cholecystectomy. The mean postoperative hospital stay was 1.8 days. Conclusion Complication rate is high in early learning phase of laparoscopic surgery which can be reduced with proper training of surgeons and they should perform these procedures under supervision of experienced laparoscopic surgeons during their learning phase. Keywords: Laparoscopic Cholecystectomy, Complications, Laparoscopy.